LEGALITAS JASA TRANSPORTASI ONLINE DALAM PERSPEKTIF PENGATURAN LALU LINTAS DAN ANGKUTAN JALAN - Nur Afit Santoso; Afif Hasbullah; Muwahid Muwahid (Universitas Islam Darul Ulum, 2020)
The issues discussed in this paper concerning the regulation of transportation services based on information technology in the Laws and Regulations. And the legality of information technology-based transportation services in the perspective of Law no. 22 of 2009 on Road Traffic and Transport (UU LLAJ). This paper uses a normative juridical research type, using a statute approach, conceptual approach and analitycal approach. The information technology-based transportation services are regulated in the LLAJ Law, Government Regulation Number 74 Year 2014 on Road Transportation (PP No. 74 Year 2014), and Regulation of the Minister of Transportation Number 118 Year 2018 on the Implementation of Special Rental Transportation (Permenhub No. 118 Year 2018). Regarding the legality of information technology-based transportation services in the perspective of LLAJ Law, it is said to be legal if it is subject to the provisions of Permenhub. 118 of 2018.